THE PHYSICAL ESSENCE OF THE VOLT-AMPERE CHARACTERISTICS OF SOLAR CELLS - Yusupov Abdurashid Khamidillaevich (World Scientific Research Journal, 2025)
Abctract: To determine the photovoltaic efficiency of solar cells, it is necessary to obtain a volt-ampere characteristic. This work discusses the mechanism of converting light energy into electrical energy in a solar cell, as well as the methods for obtaining and describing the volt-ampere characteristic.